On the average order the number of divisors of a positive integer n, and the number of distinct prime divisors of n (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
Let (n) denote the number of divisors of a positive integer n, and let (n) is the number of distinct prime divisors of n. De Koninck and Ivic [1] have been proved the asymptotic formula for .